2018
DOI: 10.1002/jia2.25098
|View full text |Cite
|
Sign up to set email alerts
|

Pressured HIV testing “in the name of love”: a mixed methods analysis of pressured HIV testing among men who have sex with men in China

Abstract: Introduction HIV testing has rapidly expanded into diverse, decentralized settings. While increasing accessibility to HIV testing is beneficial, it may lead to unintended consequences such as being pressured to test. We examined the frequency, correlates and contexts of pressured HIV testing among Chinese men who have sex with men (MSM) using mixed methods.MethodsWe conducted an online survey of MSM (N = 1044) in May 2017. Pressured HIV testing was defined as being forced to test for HIV. We conducted logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 18 publications
(15 reference statements)
1
23
0
Order By: Relevance
“…Our study found minimal potential harms associated with syphilis self-testing. The frequency of pressured testing, violence, and coercion after testing observed in our sample was similar to that reported in HIV self-testing in Malawi [42] and in China [26][27][28]. Although the experience of being pressured to take STI tests was perceived to be negative, it could potentially lead to positive change and the adoption of risk-mitigation behaviors.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our study found minimal potential harms associated with syphilis self-testing. The frequency of pressured testing, violence, and coercion after testing observed in our sample was similar to that reported in HIV self-testing in Malawi [42] and in China [26][27][28]. Although the experience of being pressured to take STI tests was perceived to be negative, it could potentially lead to positive change and the adoption of risk-mitigation behaviors.…”
Section: Discussionsupporting
confidence: 76%
“…Although the experience of being pressured to take STI tests was perceived to be negative, it could potentially lead to positive change and the adoption of risk-mitigation behaviors. A prior study documented that HIV testing frequency subsequently increased for the majority of participants who reported that they had been pressured to take an HIV test [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, women found the ability to bring kits home increased their autonomy and left them feeling empowered by testing themselves and offering HIVST to their male partners. Empowerment for women did leave some men feeling “coerced” to self‐test ; however, most described it as well‐intentioned and socially acceptable within their established partnership , as also reported for men who have sex with men from China . Nevertheless, several cases of coercion escalated into other forms of harm.…”
Section: Discussionmentioning
confidence: 95%